ANALYSIS OF DEFORMATION OBSERVATION IN TRANSCARPATHIA - KRAVETS, S.; MALYTSKYI, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of deformation observations on the permanent geophysical station "Beregovo" in Transcarpathia during 2007-2008 years using the lazer recorder designed in CB IGP NASU аre presented. The influences of different atmospheric factors, in particular temperature, upon measurement data are considered. The comparisons of deformation data with theoretically calculated tidal force are done. Some particularities of deformation data obtained during seismic phenomena’s (earthquakes) are described.